Correlation of factorial weights of separate motor coordination structure indicators, which characterize motor function level of different age groups' schoolchildren - O.V. Baginska (H.S. Skovoroda Kharkov National Pedagogical University, 2017)
Purpose: to find out correlation of the most significant indicators' factorial weights, which characterize motor coordination structure of different age groups' schoolchildren. Material: in the research 901 schoolchildren of age from 6 to 15 years participated (466 boys and 435 girls). We used computer stabiloanalyzer with biological feedback. Results: we the received factorial loads of separate indicators of motor coordination structure. Correlation of the weights showed change of their significance in the process of effective motor behavior's ensuring. We found body proportions changes' substantial influence on formation of compensatory mechanisms in sustaining body vertical position as well as the most important indicators of motor coordination structure, which have noticeable specific weight for all age groups. Conclusions: the received data can be used for modeling the process of schoolchildren's motor function's development. Factorial weights and their correlations facilitate optimization of motor function's development methodic in the process of physical culture and sports' practicing.